Global embodied mineral flow between industrial sectors: A network perspective. (October 2018) - Jiang, Meihui; An, Haizhong; Guan, Qing; Sun, Xiaoqi
Abstract: Embodied resource accounting and flow tracking are drawing increasing attention in the economy and environment issues. Differing from previous studies, this paper focus on embodied minerals, including non-metallic minerals and metals. This article proposes a systemic framework to estimate the global embodied mineral flows between sectors using multi-regional input-output analysis. Then, a global embodied mineral flow network is established, based on complex network theory, to explore the structure characteristics of embodied mineral flows. The results firstly show there is significant small-world property in the global embodied mineral flow network. Most sectors can have indirect connection with other sectors via a few sectors. Secondly, the network topology shows that a few important sectors play different roles. For example, Other Non-Metallic Mineral in China is the most important consumer of embodied minerals. The sectors' roles can be used to find the key points in the global embodied mineral flows. Thirdly, the results indicate that the embodied mineral flows have strong directionality. It includes: (1) Embodied minerals mainly flows within countries. China, the USA and India are important embodied mineral consumers. (2) Embodied mineral flows commonly follow fixed connections between sectors, such as Construction → Other Non-Metallic Mineral, which helps locate the target of resource adjusting. Finally, the policy implications for different countries are proposed. Highlights: Global embodied mineral flows are accounted. Global embodied mineral flow network is constructed. The different roles played by each country and sector are recognized. China has lower mineral usage efficiency than other countries.